Does ultrasound imaging of the spastic muscle have an additive effect on clinical examination tools in patients with cerebral palsy?: A pilot study - AKBAŞ, FIRAT; YAĞCI, İLKER; AKGÜLLE, AHMET HAMDİ; KARADAĞ SAYGI, NAİME EVRİM (My University, 2022)
OBJECTIVE: The Modified Ashworth Scale, the Modified Tardieu Scale, and measuring the passive range of motion is commonly preferred examination tools for spasticity in cerebral palsy (CP). Ultrasonography has become increasingly used to provide relevant insight into spastic muscle morphology and structure recently. It was aimed to reveal associations between the clinical and ultrasonographic parameters of gastrocnemius medialis (GM) and lateralis muscles in this population. METHODS: Thirty-four children with spastic CP aged between 4 and 12 years who did not have botulinum neurotoxin A intervention within 6 months or had no previous history of any orthopedic or neurological surgery were included. The spasticity of GM and lateralis was evaluated firstly by the Modified Ashworth Scale, Modified Tardieu Scale, and ankle passive range of motion. Then, the cross-sectional area (CSA), muscle thickness (MT), qualitative and quantitative echo intensity (EI) values of both muscles were measured from their ultrasonographic images. RESULTS: The CSA of GM, and qualitative EI of both muscles were found to be mild-to-moderately correlated to all clinical examination tools (p<0.01), whereas the CSA of gastrocnemius lateralis was mildly related to Modified Ashworth Scale (p=0.009). The MT and quantitative EI of both muscles were not associated with any of the clinical tools (p>0.05). CONCLUSION: Ultrasonographic measurements of GM and lateralis partially reflect ankle spasticity in children with CP. Ultrasonography can be used as an alternative tool in this patient population where the clinical evaluation can not perform ideally.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Gastrocnemius; spastic cerebral palsy; ultrasound imaging; TOXIN TYPE-A; CHILDREN; GASTROCNEMIUS; ARCHITECTURE; STROKE; RELIABILITY; PARAMETERS; HEALTHY; Gastrocnemius; spastic cerebral palsy; ultrasound imaging